\(\dfrac{6^3+3\cdot6^2+3^3}{-13}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 7 2018

\(\dfrac{6^3+3.6^2+3^3}{-13}\)=\(\dfrac{3^3.2^3+3.2^2.3^2+3^3}{-13}\)=\(\dfrac{3^3\left(2^3+2^2+1\right)}{-13}\)

=\(\dfrac{3^3.13}{-13}\)=\(-3^3\)=\(-27\)

16 tháng 7 2018

\(\frac{6^3+3.6^2+3}{-13}\)

\(=\frac{216+108+27}{-13}\)

\(=\frac{351}{-13}\)

\(=-27\)

16 tháng 7 2018

\(\frac{6^3+3\cdot6^2+3^3}{-13}=\frac{216+108+27}{-13}\)

\(=\frac{351}{-13}=\frac{27\cdot13}{-13}=-27\)

Bài 2:

1: =>5x+1=6/7 hoặc 5x+1=-6/7

=>5x=-1/7 hoặc 5x=-13/7

=>x=-1/35 hoặc x=-13/35

2: =>x-1=4

=>x=5

3: =>3x-1=3

=>3x=4

=>x=4/3

4: \(\Leftrightarrow\dfrac{5}{x+3}=\dfrac{-5}{6}+\dfrac{1}{2}=\dfrac{-5+3}{6}=\dfrac{-2}{6}=\dfrac{-1}{3}\)

=>x+3=-15

=>x=-18

7: \(\Leftrightarrow2^{2x+1}+2^{2x+6}=264\)

=>2^2x+1*(1+2^5)=264

=>2^2x+1=8

=>2x+1=3

=>x=1

9: =>x^4=8x

=>x^4-8x=0

=>x=2

24 tháng 9 2019

đi rồi làm cho

24 tháng 9 2019

\(\frac{6^3+3\cdot6^2+3^3}{-13}\)

\(=\frac{6^2\cdot\left(6+3\right)+3^3}{-13}\)

\(=\frac{6^2\cdot3^2+3^3}{-13}\)

\(=\frac{3^3\cdot\left(6^2+3\right)}{-13}\)

\(=\frac{3^3\cdot39}{-13}\)

\(=-3^3=-27\)

31 tháng 7 2017

a) \(\frac{4^2.4^3}{2^{10}}\)\

\(=\frac{4^5}{\left(2^2\right)^{10}}=\frac{4^5}{4^{10}}=\frac{1}{4^5}\)

b) \(\frac{0,6^5}{0,2^6}=\frac{\left(0,2.3\right)^5}{0,2^6}=\frac{0,2^5.3^5}{0,2^6}=\frac{3^5}{0,2}=5.3^5\)

14 tháng 8 2016

\(\frac{6^3+3.6^2+3^2}{-13}\)

\(=\frac{\left(2.3\right)^3+3.\left(2.3\right)^2+3^2}{-13}\)

\(=\frac{2^3.3^3+\left(3.3^2\right).2+3^2}{-13}\)

\(=\frac{3^2.\left(2^3.3+3.2+1\right)}{-13}\)

\(=\frac{3^2.31}{-13}\)

\(=\frac{9.31}{-13}\)

\(=\frac{273}{-13}\)

\(=-21\)

10 tháng 11 2018

a) \(\dfrac{-3}{5}.51\dfrac{11}{13}+\dfrac{3}{5}.21\dfrac{11}{13}\)

\(=\dfrac{-3}{5}.\left(51\dfrac{11}{13}-21\dfrac{11}{13}\right)\)

\(=\dfrac{-3}{5}.30\)

\(=-18.\)

b) \(\left|\dfrac{-3}{4}\right|.\left|-\dfrac{2}{3}\right|=\dfrac{3}{4}.\dfrac{2}{3}=\dfrac{1}{2}\).

c) \(\dfrac{-3}{5}+5\dfrac{1}{13}-\dfrac{2}{3}+1\dfrac{3}{5}-\dfrac{11}{33}\)

\(=\left(1\dfrac{3}{5}-\dfrac{3}{5}\right)+5\dfrac{1}{13}-\left(\dfrac{2}{3}+\dfrac{11}{33}\right)\)

\(=1+\dfrac{66}{13}-1\)

\(=\dfrac{66}{13}.\)

d) \(\dfrac{3}{4}.\sqrt{16}-10.\sqrt{0,81}\)

\(=\dfrac{3}{4}.4-10.\dfrac{9}{10}\)

\(=3.9\)

\(=27.\)

e) \(\left(\dfrac{3}{4}\right)^3:\left(\dfrac{-3}{8}\right)^3=\dfrac{3^3}{4^3}.\dfrac{\left(-8\right)^3}{3^3}=\left(\dfrac{-8}{4}\right)^3=\left(-2\right)^3=-8\)

f) \(\dfrac{6^4.15^3}{8.9^3.10^3}=\dfrac{2^4.3^4.3^3.5^3}{2^3.3^6.2^3.5^3}=\dfrac{2.3^7}{2^3.3^6}=\dfrac{3}{2^2}=\dfrac{3}{4}.\)

Bài 2:

a: =>x^2=60

=>\(x=\pm2\sqrt{15}\)

b: =>2^2x+3=2^3x

=>3x=2x+3

=>x=3

c: \(\Leftrightarrow\sqrt{\dfrac{1}{2}x-2}\cdot\dfrac{1}{2}=1\)

\(\Leftrightarrow\sqrt{\dfrac{1}{2}x-2}=2\)

=>1/2x-2=4

=>1/2x=6

=>x=12